Pelatihan Tarik Kapal Ikan Ukuran Kecil untuk Penentuan Tahanan dan Daya Kapal di Kabupaten Takalar - Suandar Baso; Muhammad Akbar Asis; Rosmani Rosmani; Lukman Bochary; Mansyur Hasbullah; A.Dian Eka Anggriani (JURNAL TEPAT : Teknologi Terapan untuk Pengabdian Masyarakat, 2023)
The ship's resistance is important to know because correlates strongly to the power engine needs to reach the desired speed. One method can be applied on a small ship with full-scale free running within a ways pull small ship with other small ship for measure resistance value occurrence with scale equipment on the place between the ropes of the ship being towed and tugged. This method is very easy to apply to small ships. In general, manufacturers of traditional small ships do not carry out the full-scale test because they do not know the principles for determining engine power.